Effects of biochar and alkaline amendments on cadmium immobilization, selected nutrient and cadmium concentrations of lettuce (Lactuca sativa) in two contrasting soils - Woldetsadik, D.; Drechsel, Pay; Keraita, Bernard N.; Marschner, B.; Itanna, F.; Gebrekidan, H. (Springer, 2016)
To assess the efficiency of seven treatments including biochars produced from dried faecal matter and manures as stabilizing agents of cadmium (Cd)-spiked soils, lettuce was grown in glasshouse on two contrasting soils. The soils used were moderately fertile silty loam and less fertile sandy loam and the applied treatments were 7 % w/w. The reduction of bioavailable Cd (ammonium nitrate extractable) and its phytoavailability for lettuce were used as assessment criteria in the evaluation of stabilization performance of each treatment. Moreover, the agronomic values of the treatments were also investigated. Ammonium nitrate extraction results indicated that faecal matter biochar, cow manure biochar and lime significantly reduced bioavailable Cd by 84–87, 65–68 and 82–91 %, respectively, as compared to the spiked controls. Unpredictably, coffee husk biochar induced significant increment of Cd in NH4NO3 extracts. The immobilization potential of faecal matter biochar and lime were superior than the other treatments. However, lime and egg shell promoted statistically lower yield and P, K and Zn concentrations response of lettuce plants compared to the biochar treatments. The lowest Cd and highest P tissue concentrations of lettuce plants were induced by faecal matter and cow manure biochar treatments in both soils. Additionally, the greatest Cd phytoavailability reduction for lettuce was induced by poultry litter and cow manure biochars in the silty loam soil. Our results indicate that faecal matter and animal manure biochars have shown great potential to promote Cd immobilization and lettuce growth response in heavily contaminated agricultural fields.